Reproducing vertical human walking loads on rigid level surfaces with a damped bipedal inverted pendulum. (October 2021) - Lin, Bintian; Zhang, Qingwen; Fan, Feng; Shen, Shizhao
Abstract: This study is motivated by the lack of a systematic way to reproduce vertical human walking loads with a damped bipedal inverted pendulum (DBIP). Measurements of vertical human walking loads for a sample of 16 Chinese test subjects were carried out with a non-commercial force plate on rigid surfaces, in which 2393 single-step forces were recorded and analyzed. The mean value of all the test subjects' average step frequency of free walking is 1.73 Hz, which is lower than the reported data for other populations. Most test subjects are naturally slow walkers, whose first four harmonics dynamic load factors are found to be less than the well-reported data. Only the first harmonic dynamic load factor has a clear trend to increase with the step frequency. The best linear fitting curve is given in the form of y  =  a ( x  +  b ), in which a  = 0.24 and b  = −0.82. A previously developed DBIP, which can be described by four dimensionless parameters, i.e. the dimensionless energy input, leg stiffness, leg damping, and the attack angle, is then applied to reproduce these measured forces. The simulated force with a minimum root of the mean square error to the measured force is selected and calibrated to the required step frequency and amplitude, which usually has a smaller peak force compared with the measured data. The adopted model inputs are illustrated as functions of step frequencies. The DBIP is applicable for modelling part of the test subjects' walking loads on rigid surfaces at different step frequencies.